New strategies to advance pre/diabetes care: integrative approach by PPPM - Mozaffari, Mahmood S. (Advances in Predictive, Preventive and Personalised Medicine, 2013)
The writings of earliest civilizations reveal that diabetes mellitus has afflicted man for a very long time. Unfortunately, however, we are now experiencing a world-wide pandemic of the disease which has not been adequately addressed.  Available evidence suggests that worldwide every 10 seconds one patient dies of diabetes and its severe complications.  The outlook is even more bleak with the prediction of half of a billion diabetic patients by the year 2030.  The cost-impact of the disease poses a major challenge for both developed and developing countries and their economies. Thus, it is high time to reconsider and revise the current strategies in diabetes care.  Accordingly, a paradigm shift from reactive to perspective medicine has become a timely consideration.  This shift is based on the concept of Predictive, Preventive and Personalized Medicine (PPPM). The rationale for PPPM relates to the recognition that prediction of persons at high risk for the disease (i.e., diabetes mellitus) should help devise strategies to prevent its target organ complications, and create effective treatments tailored to the individual patient, thereby reducing morbidity, and associated costs, and mortality. The current book entitled "New Strategies to Advance Pre/Diabetes Care: Integrative Approach by PPPM" is intended to serve as a reference source for researchers and the healthcare industry with a special emphasis on health promotion in the general population and help design innovative strategies to prevent the onset of diabetes mellitus and its secondary complications.